ALGORITHM FOR REPAIRING SECONDARY MAXILLARY DEFORMITIES IN PATIENTS WITH UNI- AND BILATERAL CLEFT LIP AND PALATE AFTER PRIMARY LIP AND PALATE SURGERIES - Sharopov Sanzhar Gayratovich; Tojiev Feruz Ibodullo Ugli; Azimov Mukhammadjon Ismoilovich; Inoyatov Amrillo Shodiyevich (Scholar Express Journals, 2023)
Treatment of patients with congenital facial clefts accompanied by dento-mandibular anomalies and nasal deformities is one of the most difficult tasks of modern dentistry and maxillofacial surgery. Providing qualified care to this group of patients involves multistage surgical interventions, constant dispensary observation and treatment by a number of specialists - surgeons, orthodontists, speech therapists, paediatricians, otorhinolaryngologists.
Keywords: secondary maxillary deformity; cleft; upper lip